(untitled) (Proceedings of the International Conference on Public Health, 2025)
Lung cancer is the most common cancer and the leading cause of cancer death worldwide. One-third of non-small cell lung cancer (NSCLC) patients are diagnosed in resectable stage, for which curative surgery is the cornerstone of treatment. Adjuvant osimertinib, a third-generation epidermal growth factor receptor tyrosine kinase inhibitor (EGFR TKI), was shown to significantly reduce recurrence and prolong survival for completely resected EGFR-mutated NSCLC. We performed a cost-effectiveness analysis of adjuvant osimertinib compared to placebo in patients with resected stage IB to IIIA EGFR-mutated NSCLC using Thailand’s societal perspective. A Markov model estimated the lifetime costs and health benefits of osimertinib versus placebo, including three health states: disease-free, recurrent disease, and death, tracked over a lifetime using 4-week cycles. Results were reported as 2023 USD incremental cost-effectiveness ratios (ICERs) per quality-adjusted life year (QALY) gained. The result showed that a virtual patient receiving osimertinib had 2.36 more QALYs than one receiving the placebo, at an incremental cost of 62,604.90 USD. Compared to the placebo group, treatment with adjuvant osimertinib had an ICER of 26,474.02 USD/QALY gained. Therefore, osimertinib was not cost-effective at the Thai willingness-to-pay (WTP) threshold of 4,619 USD/QALY gained. The drug price would need to be reduced by at least 85.07% for osimertinib to be cost-effective. In summary, adjuvant osimertinib for resected EGFR-mutated NSCLC patients is not cost-effective according to Thailand’s current WTP threshold. Negotiating drug costs and managed entry agreements could improve patient access to this effective treatment.